Contribution of Climate Change and Human Activities to Runoff and Sediment Discharge Changes Based on Budyko Theory and Water–Sediment Relationships during 1960–2019 in the Taohe River Basin, China - Yali Ma; Dongyuan Sun; Zuirong Niu; Xingfan Wang (Atmosphere, 2023)
Variations in runoff and sediment discharge are important characteristic variables for revealing the coupled effects of climate change (including both the natural variability of climate and anthropogenic climate change) and human activities (including soil and water conservation measures, land use changes, and hydraulic engineering construction). Based on the meteorological data from 19 meteorological stations and the hydrological data from the watershed control station of Hongqi Station, the temporal and spatial evolution of runoff and sediment discharge and the water–sand relationship were analyzed, and the response mechanisms of runoff and sediment discharge changes were clarified using Mikhail Budyko’s theory and other qualitative and quantitative methods. The results determined that: (1) The runoff and sediment discharge showed significant downward trends, with linear change rates of −0.28 × 108 m3/a and −46.10 × 104 t/a, respectively. The change points of the runoff and sediment discharge occurred in 1987 and 1996, respectively. (2) The spatial distribution of water and sediment was different, and the upper and middle reaches produced water, while the downstream produced sediment. (3) Comparing potential evapotranspiration and rainfall based on Budyko theory and the regression relationship, runoff is more closely related to rainfall, and runoff changes are more affected by it. The change in sediment discharge is most closely related to sediment concentration, followed by rainfall and potential evaporation. (4) The contribution rates of runoff and sediment discharge changes influenced by climate change were 24% and 3%, respectively, and the contribution rates by human activities were 76% and 97%, respectively. Human activities, including soil and water conservation measures, land use changes, and hydraulic engineering construction were the main influencing factors, and the impacts of human activities increased from 1960 to 2019. The research results are of great significance for erosion control and ecological restoration in the Tao River Basin under the conditions of the changing environment.